Correlation between some immunological parameters and clinical presentation in RA patients - Abbas, Nahida R.; AL- Obeidy, Eman Sh.; AL- Naim, Samira N.; Kadim, Ali E. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Complement (C) & CRP in patients with Rheumatoid arthritis (RA)’could be trigger disease activity. Aim: To study the correlation between C, CRP, IgM, IgG, IgA & some clinical presentation in RA patients. Methods: Latex agglutination test(AG) & single radial immunoassay(SRIA) were used to asses CRP, IgMJgGJgA, C, in 74 patients with RA. Results: IgA & IgG were significantly increased, while the mean ofC3, C4 were slightly elevated in RA patients . Conclusion: There is correlation between IgG and IgM with joint deformity and joint swelling respectively, while C3 was showed statistically significant P<0.01 with joint stiffness, joint swelling and Rheumatoid nodule, where as CRP was statistically significant P<0.01withjoint swelling.. Key words : RA.C.CRP, IgM, IgG, IgA, SRI A, AG.